2023
DOI: 10.3389/fimmu.2023.1140714
|View full text |Cite
|
Sign up to set email alerts
|

Long-term systemic and mucosal SARS-CoV-2 IgA response and its association with persistent smell and taste disorders

Abstract: IntroductionCurrent approved COVID-19 vaccines, notably mRNA and adenoviral vectored technologies, still fail to fully protect against infection and transmission of various SARS-CoV-2 variants. The mucosal immunity at the upper respiratory tract represents the first line of defense against respiratory viruses such as SARS-CoV-2 and is thus critical to develop vaccine blocking human-to-human transmission.MethodsWe measured systemic and mucosal Immunoglobulin A (IgA) response in serum and saliva from 133 healthc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…This observation, however modest, was particularly evident in relation to circulating IgA levels, which were negative or close to the positivity threshold in individuals who experienced a breakthrough infection or reinfection. The extend of circulating IgA contribution to protection against infection is not clear and discrepancies regarding its association with mucosal IgA have been reported [42][43][44][45][46] . Circulating IgA function has been described in relation to induction of proinflammatory cellular functions, such as phagocytosis, antibody-dependent cellular cytotoxicity (ADCC), degranulation, antigen presentation, and release of inflammatory mediators 47,48 .…”
Section: Days From First Vaccine Probability Of Positive Iga Responsementioning
confidence: 99%
“…This observation, however modest, was particularly evident in relation to circulating IgA levels, which were negative or close to the positivity threshold in individuals who experienced a breakthrough infection or reinfection. The extend of circulating IgA contribution to protection against infection is not clear and discrepancies regarding its association with mucosal IgA have been reported [42][43][44][45][46] . Circulating IgA function has been described in relation to induction of proinflammatory cellular functions, such as phagocytosis, antibody-dependent cellular cytotoxicity (ADCC), degranulation, antigen presentation, and release of inflammatory mediators 47,48 .…”
Section: Days From First Vaccine Probability Of Positive Iga Responsementioning
confidence: 99%
“…Commonly used mRNA vaccines targeting the CoV2 S protein have been shown to be efficacious in K18 mice by generating robust antibody responses ( 56 60 ). Similarly, IgM ( 61 65 ), IgG ( 26 28 , 66 69 ), and IgA ( 66 , 70 72 ) mouse antibody kinetics mirroring those observed in humans have been demonstrated. While the vast majority of these vaccine studies have centered on antibody responses, T cell responses have also been characterized ( 72 74 ).…”
Section: Preclinical Insights Gained Through Sars-cov and Sars-cov-2 ...mentioning
confidence: 56%
“…These results are consistent with other studies that have identified clear differences in humoral immune responses between vaccine-only groups and hybrid immune groups. 47,56,57 These results suggest that development of anti-SCV2 spike IgA and SIgA in the saliva requires antigen exposure in the NALT to generate a local mucosal immune response through activation of tissue-resident memory B cells.…”
Section: Discussionmentioning
confidence: 91%